An assessment of social and environmental impacts of a new shale gas industry in the Vale of Pickering, North Yorkshire. Issue 7 (2nd July 2020) - Burbidge, Manon K.; Adams, C. A.
ABSTRACT: Despite the current moratorium, shale gas has been posited by the United Kingdom's government as an important indigenous source of natural gas, a result of heightened concerns over national energy security and dwindling conventional fossil fuel reserves. Although several petroleum development licenses were awarded in the Vale of Pickering area of North Yorkshire in 2015, little research exists at the nexus of social and natural sciences on shale gas developments, particularly on potential risks to communities and the environment in the UK. This study uses the concept of energy justice and an interdisciplinary spatial assessment of potential environmental risks arising from shale gas developments, to evaluate where injustices may emerge, using the Vale of Pickering as a case study. A novel methodology was used to model a possible scenario of shale gas developments, including the spatial dimensions of air and water pollution, seismicity and traffic flows, which were combined to generate an overall environmental risk assessment. This was analysed with a metric of socio-economic vulnerability, to highlight social groups which may be disproportionately at risk from fracking. Overall, modelled proximity-based risk under this scenario did not disproportionately increase in areas with higher populations of socio-economically vulnerable groups, however potential areas for other forms of energy injustices to emerge, such as benefit-sharing injustice were found. This study offers a holistic method for identifying and understanding the local socio-environmental justice dimensions of national energy projects, such as shale gas developments, considerations which can be integrated into future planning processes.